2014
DOI: 10.1039/c4ra11818a
|View full text |Cite
|
Sign up to set email alerts
|

Calixarene modified montmorillonite: a novel design for biosensing applications

Abstract: Here we report the synthesis, characterization and application of calixarene (Calix) modified montmorillonite (Mt) as a platform for bio-applications such as biomolecule immobilization and biosensing technologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…The aim of this work was the synthesis of a new calixarene-based fluorogenic chemosensor and an efficient extractant towards hazardous dichromate anion. For this purpose, calix [4]arene diester (3) [26][27][28] was treated with diethylene triamine in a mixture of toluene and EtOH (1:1) to obtain calix [4]triazacrown-5 (4) [29,30] at cone conformation (see Scheme 1). A simple Schiff's base reaction for calix [4] triazacrown-5 (4) with 9-anthracenecarboxaldehyde in a mixture of THF and MeOH (1:3) gave a new calixarene derivative (Ant-AzClx)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The aim of this work was the synthesis of a new calixarene-based fluorogenic chemosensor and an efficient extractant towards hazardous dichromate anion. For this purpose, calix [4]arene diester (3) [26][27][28] was treated with diethylene triamine in a mixture of toluene and EtOH (1:1) to obtain calix [4]triazacrown-5 (4) [29,30] at cone conformation (see Scheme 1). A simple Schiff's base reaction for calix [4] triazacrown-5 (4) with 9-anthracenecarboxaldehyde in a mixture of THF and MeOH (1:3) gave a new calixarene derivative (Ant-AzClx)…”
Section: Resultsmentioning
confidence: 99%
“…The compounds p-tert-butylcalix [4]arene (1), calix [4]arene (2), 1,3-Odimethyl ester calix [4]arene derivative (3) and calix [4]triazacrown-5 (4) were synthesized according to literature procedures. [26][27][28][29][30] The anthracene functionalized calix [4]triazacrown-5 (Ant-AzClx) is synthesized here for the first time. To a mixture of calix [4]triazacrown-5 (4) (542.7 mg, 0.834 mmol) in CH 3 OH (10 ml) were added a solution of 9-anthracene carboxaldehyde (0.206 g, 1.0 mmol) in 10 ml tetrahydrofuran (THF), and the reaction mixture was stirred under reflux.…”
Section: The Synthesis Of Organic Compoundsmentioning
confidence: 99%
“…Enzymatic glucose biosensors based on nanoclays have recently acquired attention due to their good performance in terms of detection limit, stability, sensibility, and selectivity for in vitro glucose determination from human biological fluids [57][58][59]. Several authors have applied raw and functionalized clays in biosensors' preparation for glucose detection, as stated in Table 5 [60][61][62][63][64][65][66][67][68][69][70][71][72]. A schematic representation of an enzyme biosensor based on electrode with nanoclay for glucose determination is shown in Figure 3 [23].…”
Section: Glucose Determinationmentioning
confidence: 99%
“…Sonmez et al [63] reported the synthesis, characterization, and application of calixarene (Calix)-modified montmorillonite as a platform for biomolecule immobilization and biosensing. This modification enhanced the biomolecule immobilization capability of Mt.…”
Section: Glucose Determinationmentioning
confidence: 99%
“…7 Mt has the widest application potential in bio-based detection technologies due to attainability, well identified intercalation/exfoliation chemistry, and high surface area. In our previous studies, methyl amine, dimethylamine, 8 trimethylamine, 9 amino acid (glycine, lysine, and glutamic acid, histidine), 10,11 and calixarene 12 intercalated Mt were used as attachment platforms to prepare glucose oxidase, pyranose oxidase (POx), laccase and microbial biosensors. Clay nanocomposites also have attracted a lot of attention in recent years.…”
Section: Introductionmentioning
confidence: 99%